2017
DOI: 10.1016/j.neuroscience.2016.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Paternal deprivation affects social behaviors and neurochemical systems in the offspring of socially monogamous prairie voles

Abstract: Early life experiences, particularly the experience with parents, are crucial to phenotypic outcomes in both humans and animals. Although the effects of maternal deprivation on offspring well-being have been studied, paternal deprivation (PD) has received little attention despite documented associations between father absence and children health problems in humans. In the present study, we utilized the socially monogamous prairie vole (Microtus ochrogaster), which displays male-female pair bonding and bi-paren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 106 publications
3
39
0
Order By: Relevance
“…In recent decades, oxytocin, a neuropeptide produced in the hypothalamus that is involved in various social behaviours, 3‐8 has received attention as a potential treatment for social deficits in ASD. Substantial studies have shown that the application of intranasal oxytocin influences social cognition, empathy, social affiliation and reciprocity of healthy individuals 7‐9 .…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, oxytocin, a neuropeptide produced in the hypothalamus that is involved in various social behaviours, 3‐8 has received attention as a potential treatment for social deficits in ASD. Substantial studies have shown that the application of intranasal oxytocin influences social cognition, empathy, social affiliation and reciprocity of healthy individuals 7‐9 .…”
Section: Introductionmentioning
confidence: 99%
“…Variation in parental composition (such as manipulating the presence or absence of fathers during the rearing period) has been shown to alter the rate at which prairie vole pups develop (Wang & Novak 1992). This variation also impacts social affiliation towards conspecifics in adulthood (Tabbaa et al 2017) and the species-typical pair-bonding behavior of adult animals (Ahern & Young 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In California mice, removal of the father 3 days postpartum had no effect on the anxiety of the adult offspring tested in an empty open-field arena, but the subjects showed reduced social interactions and increased aggression (Bambico et al, 2015). In prairie voles, removal of the father a day after birth had no effect on the anxiety levels of adult offspring tested on the elevated plus maze but increased their social affiliation toward a conspecific (Tabbaa et al, 2017). However, with removal of the father 2 days before birth, the adult offspring displayed delayed partner preference and were less parental.…”
Section: Discussionmentioning
confidence: 90%